Myanmar : 2017 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that Myanmar's economy stabilized in 2016/17. The new government saw a challenging first year with lower-than-expected growth of 5.9 percent in 2016/17 mainly owing to weak agriculture production and exports, and temporary suspension of some construction projects in Yangon. Inflation moderated to 6.8 percent, and the current account deficit fell to about 3.9 percent of GDP in 2016/17 from 5.1 percent 2015/16. The medium-term macroeconomic outlook remains favorable. Growth is expected to rebound to 6.7 percent in 2017/18 mainly supported by a recovering agriculture sector and exports. Higher fiscal spending anticipated in the second half of 2017/18 owing to buoyant tax revenues will also support growth.